2005
DOI: 10.1007/s11664-005-0229-8
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behavior of silver nanoparticles for low-temperature interconnect applications

Abstract: Low-temperature sintering behavior of Ag nanoparticles was investigated. The nano Ag particles used (ϳ20 nm) exhibited obvious sintering behavior at significantly lower temperatures (ϳ150°C) than the T m (960°C) of silver. Coalescence of the nano Ag particles was observed by sintering the particles at 150°C, 200°C, and 250°C. The thermal profile of the nanoparticles was examined by a differential scanning calorimeter (DSC) and a thermogravimetric analyzer (TGA). Shrinkage of the Ag-nanoparticle compacts during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
197
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 359 publications
(206 citation statements)
references
References 8 publications
8
197
0
1
Order By: Relevance
“…From Figure 8 it is clear that up to a sintering temperature range 100 • C, the electrical conductivity of pure silver pellet remains almost constant and increases slightly from 100 to 150 • C and then decrease beyond the 150 • C. While in CNT reinforced silver matrix nanocomposites (6 vol % and 12 vol %) the electrical conductivity increases within a temperature range of 35 -100 • C and then decreases at 150 • C. This is due to the presence of more pores in the matrix which provide easy path for the expansion even at low temperature. Coalescence of the Ag nanoparticles during the sintering process increases the density [19] and hence the conductivity of the nanocomposites. At higher temperature, the grain size starts increasing which further reduces the electrical conductivity.…”
Section: Low Temperature Sintering Of Ag/cnt Nanocompositesmentioning
confidence: 99%
“…From Figure 8 it is clear that up to a sintering temperature range 100 • C, the electrical conductivity of pure silver pellet remains almost constant and increases slightly from 100 to 150 • C and then decrease beyond the 150 • C. While in CNT reinforced silver matrix nanocomposites (6 vol % and 12 vol %) the electrical conductivity increases within a temperature range of 35 -100 • C and then decreases at 150 • C. This is due to the presence of more pores in the matrix which provide easy path for the expansion even at low temperature. Coalescence of the Ag nanoparticles during the sintering process increases the density [19] and hence the conductivity of the nanocomposites. At higher temperature, the grain size starts increasing which further reduces the electrical conductivity.…”
Section: Low Temperature Sintering Of Ag/cnt Nanocompositesmentioning
confidence: 99%
“…Research in the field of nanotechnology has gained significant momentum as the properties demonstrated by these structures at the nanoscale level are remarkable in terms of their applicability (Duncan 2011). Silver nanoparticles have been the prime focus of the nanoparticles' research industry due to their unique thermal (Moon et al 2005), electrical (Chen et al 2009) and optical (Kelly et al 2003) properties and also because of the use of these structures in products that range from photovoltaics (Yoon et al 2010) to biological and chemical sensors (McFarland and Van Duyne 2003). Also nanosilver has been used extensively as an anti-bacterial agent in the health industry (Jain and Pradeep 2005), food storage (Costa et al 2011), textile coatings (Perelshtein et al 2008) and also for a number of environmental applications (Li et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Moon et al investigated the thermal behavior of silver nanoparticles (size: <20 nm), and revealed that shrinkage of the silver nanoparticles occurred over the temperature range of 150-250 °C [120]. On the other hand, Auyeung et al investigated the effect of laser decal transfer to micro cantilevers, and they found that mass deduction of micro cantilevers occurs after curing at 200-400 °C [121].…”
Section: Insulating Blockmentioning
confidence: 99%